2000
DOI: 10.1046/j.1365-2443.2000.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

A human homologue of yeast anti‐silencing factor has histone chaperone activity

Abstract: Background: Structural changes in chromatin play essential roles in regulating eukaryotic gene expression. Silencing, potent repression of transcription in Saccharomyces cerevisiae, occurs near telomeres and at the silent mating-type loci, as well as at rDNA loci. This type of repression relates to the condensation of chromatin that occurs in the heterochromatin of multicellular organisms. Anti-silencing is a reaction by which silenced loci are de-repressed. Genetic studies revealed that several factors partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
143
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 99 publications
4
143
0
1
Order By: Relevance
“…These structures have been very rewarding in that they provide intriguing insights into the mechanism of nucleosome disassembly. In vitro and in vivo evidence that Asf1 binds a heterodimer of H3/H4 (and not, as previously assumed, a (H3-H4) 2 tetramer) [51] [52] [53] were confirmed by x-ray crystallography, and the structural basis for these observations became immediately obvious. Asf1 binds the C-terminal α3-helix of H3, preventing the formation of the (H3-H4) 2 through the four-helix bundle (Figure 4).…”
Section: Chaperone -Histone Interactions and Implications For Nucleosmentioning
confidence: 69%
“…These structures have been very rewarding in that they provide intriguing insights into the mechanism of nucleosome disassembly. In vitro and in vivo evidence that Asf1 binds a heterodimer of H3/H4 (and not, as previously assumed, a (H3-H4) 2 tetramer) [51] [52] [53] were confirmed by x-ray crystallography, and the structural basis for these observations became immediately obvious. Asf1 binds the C-terminal α3-helix of H3, preventing the formation of the (H3-H4) 2 through the four-helix bundle (Figure 4).…”
Section: Chaperone -Histone Interactions and Implications For Nucleosmentioning
confidence: 69%
“…First, mutation of the yeast asf1 gene results in the suppression of S-phase-specific histone genes activation (Sutton et al 2001). Second, it was shown that ASF1 interacts with bromodomain-containing subunits of TFIID (Munakata et al 2000;Chimura et al 2002).…”
Section: Asf1 Interacts With the Brahma Complex Genes And Development 2623mentioning
confidence: 99%
“…Nucleosome assembly is the process by which newly synthesized histones are loaded onto naked DNA. This function is performed primarily by histone chaperones like Chromatin Assembly Factor-1 (CAF-1) and Nucleosome Assembly Protein-1 (NAP-1; Munakata et al 2000;Philpott et al 2000;Mello and Almouzni 2001). However, nucleosome assembly factors alone are unable to efficiently produce long and regularly spaced nucleosomal arrays.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another evolutionarily conserved histone chaperone is CCG1-interacting factor A (CIA) (19), whose budding yeast homologue, anti-silencing function 1 (Asf1), has been shown to possess anti-silencing activity (20), also participates in the nucleosome reassembly reaction on the daughter DNA strands (21). Recently, CIA/Asf1 has been reported to regulate replication fork progression and histone supply and demand in the DNA replication process (22,23).…”
mentioning
confidence: 99%